The mesodermal and myogenic specification of hESCs depend on ZEB1 and are inhibited by ZEB2 - Chiara Ninfali; Laura Siles; Anna Esteve-Codina; Antonio Postigo (Cell Reports, 2023)
Summary: Human embryonic stem cells (hESCs) can differentiate into any cell lineage. Here, we report that ZEB1 and ZEB2 promote and inhibit mesodermal-to-myogenic specification of hESCs, respectively. Knockdown and/or overexpression experiments of ZEB1, ZEB2, or PAX7 in hESCs indicate that ZEB1 is required for hESC Nodal/Activin-mediated mesodermal specification and PAX7+ human myogenic progenitor (hMuP) generation, while ZEB2 inhibits these processes. ZEB1 downregulation induces neural markers, while ZEB2 downregulation induces mesodermal/myogenic markers. Mechanistically, ZEB1 binds to and transcriptionally activates the PAX7 promoter, while ZEB2 binds to and activates the promoter of the neural OTX2 marker. Transplanting ZEB1 or ZEB2 knocked down hMuPs into the muscles of a muscular dystrophy mouse model, showing that hMuP engraftment and generation of dystrophin-positive myofibers depend on ZEB1 and are inhibited by ZEB2. The mouse model results suggest that ZEB1 expression and/or downregulating ZEB2 in hESCs may also enhance hESC regenerative capacity for human muscular dystrophy therapy.